Electrochemical Investigations of dopamine by gallic acid isolated from Pterocarpus marsupium Roxb carbon paste electrode : A voltammetric study - Deepa, R; Manjunatha, H.; Krishna, V.; SWAMY, KUMARA (Research in Biotechnology, 2015)
Gallic acid was isolated from the stem bark ofÃ‚Â Pterocarpus marsupium Roxb and the obtained compound was used as the modifier to study the electrochemical investigations of dopamineÃ‚Â at modified carbon paste electrode in vitro by cyclic voltammetric technique. The effect of scan rate and concentration at modified carbon paste electrode shows the overall electrode process was both diffusion and adsorption-controlled. The same modified electrode was used for the detection of dopamineÃ‚Â in vivo by differential pulse voltammetric technique. This method can also be used for other bioactive molecules.